Effect of dietary supplementation of palm kernel cake on ovarian and hepatic function in buffalo (Bubalus bubalis) - de Souza Nahúm, Benjamim [UNESP]; Saraiva, Naiara Zoccal; Faturi, Cristian; Maciel e Silva, André Guimarães; Lourenço, José de Brito; Sousa, José Silva de; Amaral, João Maria do; de Paula Nogueira, Guilherme [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Elsevier, 2019)
To determine the optimal inclusion amount of palm kernel cake (PKC) in a buffalo diet, in the present study there was evaluation of the ovarian activity, metabolism and hepatic function of females that were treated to synchronize the time of ovulation. Twenty-four estrous-cyclic and non-lactating Murrah buffalo with a mean age of 5.7 years were supplemented with 0%, 0.25%, 0.5% and 1% of their body weight (BW) with PKC. Animals were subjected to the Ovsynch protocol (beginning of protocol = D0). The ovaries were examined and the blood was collected on D10 (follicular phase) and D17 (luteal phase). Follicular and luteal development and serum progesterone concentrations were not affected by diet (P > 0.05). Serum concentrations of cholesterol were greater in animals supplemented with PKC in amounts at 0.5% of BW or less with PKC, regardless of the phase of the estrous cycles when evaluations occurred (P < 0.05). Concentrations of HDL-cholesterol were similar (P > 0.05) during the follicular and luteal phases. Triglyceride concentrations increased linearly (P = 0.03) as percentage of PKC inclusion diets increased during the follicular phase, but were similar in the luteal phase (60.0 mg/dL; P = 0.51). Amount of PKC supplementation did not affect the concentrations of alanine aminotransferase, but there was a greater amount of aspartate aminotransferase (AST) and gamma glutamyl transferase (GGT) during both phases of the estrous cycle (P < 0.05). Animals supplemented at 1.0% of BW with PKC had greater AST and GGT concentrations than what is recommended for buffalo. The results of the present study indicate PKC supplementation of buffalo diets does not affect the development of the ovarian follicle and corpus luteum nor the peripheral concentration of progesterone, even though there are greater serum concentrations of total cholesterol and triglycerides. Because the amount of PKC supplementation in the present study does not result in hepatic dysfunction when fed at the 0.5% of BW amount, it is suggested that this agro-industrial byproduct of high nutritional value may be a new alternative for dietary supplementation of grazing buffalo.
Keywords: Buffalo; Cholesterol; Estrous synchronization; Liver function; Ovsynch